Empowering Nambo Village through physiotherapy intervention and the establishment of the Sahabat Tumbuh Kembang community - Zahra Sativani; Yusuf Nasirudin; Ari Sudarsono; Ahmad Syakib; Nur Achirda; Nina Mustikasari; Renata Amelia Putri; Mohammad Ramadhan (University of Merdeka Malang, 2026)
Infant and toddler health remains one of the crucial indicators of public health. However, Nambo Village faced challenges due to parents' limited literacy regarding developmental delays and cadres' inadequate skills in early detection and pediatric stimulation. To address the issues, a community-based physiotherapy intervention was implemented started from June to October 2025. The program aimed to empower parents and optimize cadres' capacities through the establishment of the Sahabat Tumbuh Kembang (Child Development Companionship) community. The methodology included situational analysis, socialization, implementation, and evaluation, resulting a significant improvement in understanding developmental red flags, confirmed by an increase in average scores from 7.5 (pre-test) to 9.3 (post-test). Furthermore, the knowledge was practically applied through independent early screening targeted to five cadres and one village midwife on 30 toddlers. To ensure program sustainability, the Sahabat Tumbuh Kembang community was officially formed with six driving agents. This group currently synergizes with the local Bina Keluarga Balita (Early Childhood Family Development) program to conduct monthly basic motor development monitoring, effectively realizing independent community empowerment for a healthier generation.